US Health and Aggregate Fluctuations - Aleksandar Vasilev (Bulletin of Economic Research, 2016)
This paper aims to shed light on the importance of health considerations for business cycle fluctuations and the effect of health status on labor productivity and availability of labor input for productive use. To this end, Grossman's (2000) partial-equilibrium framework with endogenous health is incorporated in an otherwise standard Real-Business-Cycle (RBC) model. Health status in this setup is modelled as a utility-enhancing, intangible, and non-transferrable capital stock, which depreciates over time. The household can improve their health ("produce health") through investment using a health-recovery technology. The main results are: (i) overall, the model compares well vis-a-vis data; (ii) the behavior of the price of healthcare is adequately approximated by the shadow price of health in the model; (iii) the model-generated health variable exhibits moderate- to high correlation with a large number of empirical health indicators.
Keywords: E32; I11; 330; real business cycles; health investment